Embedding Assessment into Daily Teaching: A Systematic Review of Classroom-Based Language Assessment - Nayla Rahma Sena; Qayla Mahmoodah Ahmad; Syamsa Farhatul Muhayya; Ratna Sari Dewi; Reza Anis Maulidya (Indonesian Journal of Education and Learning, 2026)
Classroom-based assessment (CBA) has increasingly become a central concern in language education because it links teaching, learning, and assessment in a continuous process. However, many teachers still face difficulties embedding assessment naturally into classroom practices, often relying on summative tests instead of formative approaches that support learning. This study aims to systematically review research on how assessment can be integrated into daily language teaching and what principles and challenges are commonly found in its implementation. A Systematic Literature Review (SLR) was conducted following PRISMA 2020 guidelines. Searches were carried out in Google Scholar, ERIC, and Scopus databases for peer-reviewed English-language articles published between 2015 and 2025. After identification, screening, and eligibility assessment, 16 empirical studies were included in the thematic synthesis, with six core studies selected for in-depth discussion due to their methodological rigor and relevance. The thematic analysis revealed four main themes: principles of effective classroom-based assessment, strategies for embedding assessment into daily instruction, teachers’ roles and assessment literacy, and institutional challenges influencing implementation. The findings indicate that embedding assessment into teaching enhances student engagement, supports reflective teaching, and improves learning outcomes. However, sustained professional development and institutional support remain essential for effective implementation. This review contributes to the field by providing an integrated synthesis of assessment principles, instructional practices, and contextual factors, offering a comprehensive framework for understanding how classroom-based assessment can be effectively embedded in language education.